AKTIVITAS HEMAGLUTINASI BAKTERI ACINETOBACTER BAUMANNII YANG BERASAL DARI SPESIMEN KLINIK DAN LINGKUNGAN - Noorhamdani, Noorhamdani (Jurnal Kedokteran Brawijaya, 2004)
ABSTRACT Acinetobacter baumannii (Acb) is an opportunistic or a nosocomial pathogenic bacterium which attacks immunocompromised host. Colonization and infection often occur while hospitalized and could lead to pneumonia infection, urinary tract infection, meningitis, septicemia, and burn or surgical wound infections. In spite of the steady increase of Acb infection cases, little has been revealed about the Acb infection mechanism. The infection process is initiated by the adhesion of bacteria onto the host’s cell, followed by multiplication, colonization and infection. Adhesion onto the host’s cell is mediated by the adhesin molecule functioning as the virulence factor. Adhesin is usually found in the form of hemaglutinin protein which is bound to the receptor available at the host’s cell surface. Target of research is to know weather the bacterium have hemaglutinin protein, by seeing the ability of agglutination red blood of mice 0.5%. Isolate of Acb coming from clinical specimen consisted of urine 35 isolates, sputum 27 isolates, pus 15 isolates, and blood 1 isolat.